Forensic Medical Examination of the Quality of Medical Care: Legal, Methodological and Ethical Issues - Pavlovna Grishina, Ekaterina; Valentinonva Shiryaeva, Svetlana; Aleksandrovna Sheiafetdinova, Natalia; Aleksandrovich Solovyev, Andrey (International Journal of Psychosocial Rehabilitation, 2019)
Qualified medical care is a fundamental component of the social policy of any civilized state in which a person, his life and health are recognized as the highest indisputable value and a special object of legal protection. Qualified medical care is the most important, but not the only segment of activity in the field of health care, because this assistance must be, first of all, timely, as well as quality at all levels: from examination, diagnosis and treatment, performing purely medical manipulations – to care, rehabilitation and restoration of vital functions, provided by the efforts of nurses. Poor or untimely medical care can lead to irreversible consequences for the patient: the transition of the disease to a chronic form, disability and even death. At the same time, it should be recognized that there may be situations in which, for objective or subjective reasons, even with the proper provision of medical care and services of the same name, it is not possible to cure, and sometimes to save the patient. A person whose health has deteriorated, and persons who have lost loved ones and loved ones because of an incurable disease, it is difficult to accept their situation, to realize that doctors have done everything they could, but medicine in such a situation was powerless. Unwillingness to objectively assess the situation often leads to an appeal to various state bodies (departmental, judicial and law enforcement) with a request to investigate the event, certainly to find and punish the perpetrators. One of the effective scientific and practical ways of objective resolution of such disputes is a medical examination of the quality of medical care.